2017
DOI: 10.1136/bmjopen-2016-015205
|View full text |Cite
|
Sign up to set email alerts
|

Stepped-wedge cluster-randomised controlled trial to assess the cardiovascular health effects of a managed aquifer recharge initiative to reduce drinking water salinity in southwest coastal Bangladesh: study design and rationale

Abstract: IntroductionSaltwater intrusion and salinisation have contributed to drinking water scarcity in many coastal regions globally, leading to dependence on alternative sources for water supply. In southwest coastal Bangladesh, communities have few options but to drink brackish groundwater which has been associated with high blood pressure among the adult population, and pre-eclampsia and gestational hypertension among pregnant women. Managed aquifer recharge (MAR), the purposeful recharge of surface water or rainw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…The first cohort study followed up 383 participants for two visits (742 person-visits) from southwest coastal Bangladesh during the wet season [ 21 ]. The second study was a population-based stepped-wedge randomized controlled trial in southwest coastal Bangladesh that followed up 1190 participants for five monthly visits (5745 person-visits) during the dry season [ 22 , 23 ]. The third cohort study followed up 293 participants from southwest coastal and 277 from non-coastal central Bangladesh for seven visits covering both wet and dry seasons (3547 person-visits data: 1773 from coastal and 1774 from non-coastal regions) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first cohort study followed up 383 participants for two visits (742 person-visits) from southwest coastal Bangladesh during the wet season [ 21 ]. The second study was a population-based stepped-wedge randomized controlled trial in southwest coastal Bangladesh that followed up 1190 participants for five monthly visits (5745 person-visits) during the dry season [ 22 , 23 ]. The third cohort study followed up 293 participants from southwest coastal and 277 from non-coastal central Bangladesh for seven visits covering both wet and dry seasons (3547 person-visits data: 1773 from coastal and 1774 from non-coastal regions) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the midst of the dry season, ponds repeatedly dried up leaving coastal population with few or no options but to extricate saline groundwater utilizing hand pumps for drinking and cooking, whereas amidst the monsoon (May to October), coastal population generally gather rainwater through household-or-community-level rainwater harvesting schemes [31]. It is, therefore, clear, that saltwater invasion as well as salinisation partakes consumable water shortages regionally and globally around the coasts, forcing the people to be dependent on the substitute sources for water consumption [29]. Coastal communities in Bangladesh, however, had little consciousness of the dangers related with superfluous salt consumption in their food.…”
Section: Drinking Water Sodium (Dws) and Health Of Coastal Peoplementioning
confidence: 99%
“…While these interventions may be effective in reducing DWS exposure [31], MAR is a promising adaptive approach for increasing the accessibility of salt free potable water that sustains almost a yearly water supply. Since MAR storage of rainwater occur under confined conditions, it is further secured from evaporation as well as strong to tidal storms, cyclones and saltwater permeation (Figure 4) [29,35]. In MAR, a freshwater lens is purposefully created amidst the brackish aquifers, to supply with the surface freshwater or rainwater to the aquifers to bring the hydrological equilibrium.…”
Section: Interventions To Decrease Drinking Water Sodium (Dws): Are Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The Geology Department of the University of Dhaka, in collaboration with Unicef piloted 18 MAR projects, in three districts of south-west Bangladesh; Khulna, Shatkhira and Bagerhat [6].The MAR pilot study demonstrated the potential for increasing freshwater availability and sustainable year-round drinking water supplies. Subsequently 80 MAR systems have been installed in these regions and a health impact evaluation of MAR water access on blood pressure and kidney function has recently concluded [1,6,19,20].…”
Section: Introductionmentioning
confidence: 99%